1995
DOI: 10.1128/jcm.33.2.364-370.1995
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Crystal Enteric/Nonfermenter system, API 20E system, and Vitek AutoMicrobic system for identification of gram-negative bacilli

Abstract: A comparative evaluation of the Crystal Enteric/Nonfermenter system (Crystal; Becton Dickinson, Cockeysville, Md.), API 20E (API; bioMérieux Vitek, Inc., Hazelwood, Mo.), and the Vitek GNI card (Vitek; bioMérieux Vitek) was performed with 512 clinical isolates of gram-negative bacilli, including 381 members of the family Enterobacteriaceae and 131 nonenteric bacilli. With supplemental testing, API, Crystal, and Vitek correctly identified to the genus and species level 505 (98.6%), 489 (95.5%), and 494 (96.5%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 22 publications
(24 reference statements)
0
19
0
3
Order By: Relevance
“…Other evaluations of the Crystal E/NF have reported accuracies ranging from 47 to 97% after initial incubation and error rates as low as 0.8% (6,(8)(9)(10). The numbers and identifications of strains that were tested in those studies more closely represent the assortment of organisms found in clinical laboratories on a daily basis than do the organisms used in this study.…”
Section: Table 4 Errors Inmentioning
confidence: 68%
“…Other evaluations of the Crystal E/NF have reported accuracies ranging from 47 to 97% after initial incubation and error rates as low as 0.8% (6,(8)(9)(10). The numbers and identifications of strains that were tested in those studies more closely represent the assortment of organisms found in clinical laboratories on a daily basis than do the organisms used in this study.…”
Section: Table 4 Errors Inmentioning
confidence: 68%
“…1,1996), which now includes the variations in arabinose fermentation so often seen with isolates of Y. pestis, should increase the accuracy of this system. In previous studies, API correctly identified 88 to 99.4% of the enteric, nonfermentative bacteria tested (3,(5)(6)(7)(8)(9), and API 20NE correctly identified 75.3% of these bacteria (10). These older systems clearly misidentify the less reactive bacteria, which could lead to misdiagnosis.…”
mentioning
confidence: 94%
“…Salmonella infections may cause gastroenteritis, involving an abrupt onset of nausea, fever, vomiting, and diarrhea, with several virulence factors involved (Baumler et al, 1998;Schaechter et al, 2001). Some outbreaks affecting the population are caused by specific Salmonella serovars (serotypes), and the difficulty in detecting carriers makes these a potential source of contamination, particularly due to detection limitations of culture techniques, which are also time-consuming (Robinson et al, 1995;Aspinall et al, 1992).…”
Section: Introductionmentioning
confidence: 99%